Pikeperch, Sander lucioperca Invasion in the Neretva River Watershed (Bosnia and Herzegovina, Croatia) After Alteration of River Flow. (16th June 2015) - Pavličević, J.; Glamuzina, L.; Conides, A.; Savić, N.; Rozić, I.; Klaoudatos, D.; Kazić, A.; Glamuzina, B.
Abstract: The invasion history and the recent distribution, abundance and prey composition of pikeperch, Sander lucioperca in Neretva River watershed (Bosnia and Herzegovina and Croatia) are presented. The species was illegally/unintentionally introduced in Ramski Reservoir in the upper river part in 1986, while establishment of its abundant populations was reported during the 1990s in two connected artificial reservoirs. The research on the present abundance and food composition was executed during the 2012–2014 period. The results showed that pikeperch occupied most of the water bodies of the Neretva River, with an exception of natural river parts with gravel sediment and fast flow: all five artificial reservoirs (Ramski, Jablanički, Grabovica, Salakovac and Mostarski reservoirs) and lower wetland zone. However, the success and impact of colonization differ among water bodies, indicating pikeperch preference for warm and shallow reservoirs. Pikeperch prey is composed of different fish species abundant in specific water bodies. In artificial reservoirs, it preys mostly on introduced fish species, with a potential for controlling pumpkinseed abundance and biomass. Sampling carried out in Ramski Reservoir between 2013 and 1014 showed exclusive feeding on the introduced Leucaspius delineatus, and the establishment of a new food web, where only introduced species play significant roles. Copyright © 2015 John Wiley & Sons, Ltd.